INVESTMENT- BASIS OF DEVELOPMENT (IN THE EXAMPLE OF ANDIZHAN REGION) - Oybek Turdimamatovich Nurmatov (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the role of investments in the development of the economic front, the activities of joint enterprises in Andizhan region during the period of independence with the help of scientific literature and primary sources.